Acute Cellular and Functional Changes With a Combinatorial Treatment of Ion Channel Inhibitors Following Spinal Cord Injury - O’Hare Doig, Ryan L.; Santhakumar, Sreya; Fehily, Brooke; Raja, Sushmitha; Solomon, Tanya; Bartlett, Carole A.; Fitzgerald, Melinda; Hodgetts, Stuart I. (Frontiers in Molecular Neuroscience, 2020)
Reducing the extent of secondary degeneration following spinal cord injury (SCI) is necessary to preserve function, but treatment options have thus far been limited. A combination of the ion channel inhibitors Lomerizine (Lom), YM872 and oxATP, to inhibit voltage gated Ca2+ channels, Ca2+ permeable AMPA receptors and purinergic P2X7 receptors respectively, effectively limits secondary consequences of injury in in vitro and in vivo models of CNS injury. Here we investigated the efficacy of these inhibitors in a clinically relevant model of SCI. Fischer (F344) rats were subjected to a moderate (150kD) contusive SCI at thoracic level T10 and assessed at 2 weeks or 10 weeks post-injury. Lom was delivered orally twice daily and YM872 and oxATP were delivered via osmotic mini-pump implanted at the time of SCI until 2 weeks following injury. Open field locomotion analysis revealed that treatment with the three inhibitors in combination improved the rate of functional recovery of the hind limb (compared to controls) as early as 1-day post injury, with beneficial effects persisting to 14 days post injury, while all three inhibitors were present. At 2 weeks following combinatorial treatment, functional improvement was associated with significantly decreased cyst size, increased immunoreactivity of β-III tubulin+ve axons, myelin basic protein and reduced lipid peroxidation by-products, and increased CC1+ve oligodendrocytes and NG2+ve/PDGFα+ve oligodendrocyte progenitor cell densities, compared to vehicle treated SCI animals. The combination of Lom, oxATP and YM872 shows preclinical promise for control of secondary degeneration following SCI and further investigation of long-term sustained treatment is warranted.